(2x-3)=(x+5)

Simple and best practice solution for (2x-3)=(x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-3)=(x+5) equation:


Simplifying
(2x + -3) = (x + 5)

Reorder the terms:
(-3 + 2x) = (x + 5)

Remove parenthesis around (-3 + 2x)
-3 + 2x = (x + 5)

Reorder the terms:
-3 + 2x = (5 + x)

Remove parenthesis around (5 + x)
-3 + 2x = 5 + x

Solving
-3 + 2x = 5 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-3 + 2x + -1x = 5 + x + -1x

Combine like terms: 2x + -1x = 1x
-3 + 1x = 5 + x + -1x

Combine like terms: x + -1x = 0
-3 + 1x = 5 + 0
-3 + 1x = 5

Add '3' to each side of the equation.
-3 + 3 + 1x = 5 + 3

Combine like terms: -3 + 3 = 0
0 + 1x = 5 + 3
1x = 5 + 3

Combine like terms: 5 + 3 = 8
1x = 8

Divide each side by '1'.
x = 8

Simplifying
x = 8

See similar equations:

| f(10)=1546(1*0.2)x | | (3x-7)+(2x+2)=145 | | 5x-3(2y-4x)-5y= | | 3X+5X-5=115 | | 9(5+x)-6(x+3)= | | 14Xy= | | 12=g-15 | | 75=-12 | | (-3-x)(-x+3)= | | 0.2(0.5x-4)7.4=-96 | | x+1/2x-3/2x=1/6 | | v-9=-5 | | 2k^2+3k^2-7k^2= | | -4+5y=-34 | | 3.2(2x+2.1)-0.8=-1 | | y^3+2y^2=36y+32 | | 6b+6=8 | | 15=y-23 | | 6+4X+6X=126 | | -(c+d)-4d+5c-d=0 | | 3b+12+8=-3 | | (3a+b)(2a+b)= | | 2c+3c=109225 | | 2x+3y+4x+5y=0 | | 19g-4h+4-20(g-1)=0 | | x-.7=9.09 | | n+2n+4= | | 7y-27=-32+2y | | 9(k-4)=12 | | 58=-y+179 | | -11x+4+8x-4+3x=0 | | -3x-21=-81 |

Equations solver categories